2016
DOI: 10.4025/jphyseduc.v27i1.2744
|View full text |Cite
|
Sign up to set email alerts
|

Relação Entre a Competência Motora Percebida Geral, O Gênero, a Competência Motora Percebida Específica À Tarefa E a Competência Motora Real De Crianças

Abstract: RESUMOO Objetivo deste estudo foi investigar as relações entre a competência motora percebida geral (CMPG), a competência motora específica à tarefa (CMPET), a competência motora real (CMR), e o gênero de crianças. Participaram do estudo 75 crianças, de ambos os gêneros, com nove e dez anos de idades. A CMPG foi avaliada pela "Self-Perception Profile for Children". Uma escala desenvolvida pelos autores e preliminarmente validada foi utilizada para avaliação da CMPET. A CMR foi avaliada pelo Test of Gross Motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
2
2
3
Order By: Relevance
“…The locomotor and object control raw scores of Turkish children were found to be lower than the results by Ré et al (2018), which for the girls with same age were 35.8±4.3 for locomotor total and 28.8±5.1 for object control and for boys' locomotor total was 35.9±4.3 and object control total was 33.0±5.7. On the other hand, it was found to be higher than the result by Nobre et al (2016) who found that total locomotor in girls of the same age was 25.5 and object control was 26 and locomotor total for boys was 25.1 and object control total was 26.3. When the results were compared with the subtest scores given in Nobre et al (2016) individually, it showed that the lowest score of the Turkish children was for 'striking a stationary ball test', which was one of the object control subtests (2.4 ± 1.0 for girls and 3.2 ± 1.4 for boys).…”
Section: Discussioncontrasting
confidence: 73%
“…The locomotor and object control raw scores of Turkish children were found to be lower than the results by Ré et al (2018), which for the girls with same age were 35.8±4.3 for locomotor total and 28.8±5.1 for object control and for boys' locomotor total was 35.9±4.3 and object control total was 33.0±5.7. On the other hand, it was found to be higher than the result by Nobre et al (2016) who found that total locomotor in girls of the same age was 25.5 and object control was 26 and locomotor total for boys was 25.1 and object control total was 26.3. When the results were compared with the subtest scores given in Nobre et al (2016) individually, it showed that the lowest score of the Turkish children was for 'striking a stationary ball test', which was one of the object control subtests (2.4 ± 1.0 for girls and 3.2 ± 1.4 for boys).…”
Section: Discussioncontrasting
confidence: 73%
“…Outro aspecto observado nas pesquisas é a percepção mais elevada dos meninos especialmente em relação a dimensões da atlética da autoperceção de competência. Vários estudos nacionais 11,17,20,[29][30][31][32][33][34] e internacionais 26,[35][36][37][38] confirmam essa tendência. As crenças e valores culturais, especialmente em relação à atribuição de papéis sociais também têm influência sobre a construção da competência percebida.…”
Section: Auto-percepção De Competência Em Diferentes Faixas Etárias E Entre Meninos E Meninas: As Contribuicões Das Pesquisas Atuais Paraunclassified
“…A percepção mais elevada dos meninos em relação a algumas dimensões da competência percebida é outro aspecto observado nas pesquisas. Especificamente, em relação a competência atlética, frequentemente os meninos mostram maior percepção comparados as meninas, influenciados por agentes culturais que valorizam essas experiências mais fortemente em meninos 11,[13][14][15][16][17][18] . Entrentanto, outros estudos não têm observado essas diferenças [19][20][21][22] , reforçando a importância de estudos empíricos sobre fatores culturais e desenvolvimentistas que possam afetar essas percepçōes na infância.…”
Section: Introductionunclassified
“…A recent meta-analysis indicated a moderate to strong relationship between HRF and MC from early childhood to young adulthood, while acknowledging that other factors not assessed (possibly PMC) could have contributed to the strength of this relationship, warranting future research [21]. On the other hand, a recent study has challenged these theories by finding no significant relationship between PMC and MC in their sample of children [22].…”
Section: Introductionmentioning
confidence: 99%